Self-determined learning in EFL classroom: a trajectory for the future research - Deni Sapta Nugraha; Ninuk Lustyantie; Uwes Anis Chaeruman (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2022)
The development of technology has rapidly affected the growth complexity of the 21st century's work environment which also influences educational environment. Thus, approaches in teaching and learning such as self-determined learning has been considered relevant to enhance the quality of learning. Researchers and educators have been pursuing to accomodate the praxis of self-determined learning. The purpose of the study was to uncover research trends and try to bridge the gap of future research of self-determined learning (SDL) in the English as a foreign language (EFL) context. Using meta-synthesis, 13 selected articles were examined drawn from a single database from the last five years between 2017 and 2021. The articles were systematically selected through several criteria using the query